New Approaches to Forming Business Competency of Future Specialists of Restaurant Industry - Tkachenko, Mykhailo (Professional Pedagogics, 2017)
The article reveals the actual approaches to the formation of entrepreneurial competence of future specialists in restaurant industry in vocational schools, which is conditioned by geopolitical and socio-economic transformations, recognition of the priority of entrepreneurship at the present stage of the formation of a market economy, as well as relevant changes in the system of vocational education. Regarding this, in the labor market, the interest in specialists of the restaurant industry with the established entrepreneurial competence is growing, which is a complex socio- economic and psycho-pedagogical dynamic phenomenon, which ensures their competitiveness in the conditions of an unstable market economy. It is substantiated that at vocational schools this phenomenon is formed on the basis of the coherent training of future specialists of the restaurant industry for professional innovative and creative entrepreneurial activity and includes the acquisition by students of professionally meaningful qualities, namely, the ability to self-realization in the conditions of market uncertainty, self-employment (the opening of their own business), the ability to analyze the market opportunities of the enterprise and master the leading economic roles, adequately assessing their own entrepreneurial abilities and opportunities. Thus, the necessity of continuous updating and improvement of the educational process of future specialists of the restaurant industry has been formalized through the use of interactive methods and innovative approaches to the process of vocational education in the vocational schools of the culinary profile.
Keywords: vocational education; vocational schools; entrepreneurial competence; future specialists in the restaurant industry